INFORMATIKA HÁM IT PÁNINDE JOYBAR METODÍNAN PAYDALANÍWDÍŃ ZÁRÚRLIGI - Ilyasova, Z.K. (SCIENCE and SOCIETY, 2024)
The article discusses the stages, methods, results of using the project method in teaching computer science and IT in secondary schools, as well as the need.
Keywords: knowledge; skills; IT literacy; "subject-object"; “subject-subject"; project method; Design; virtual processes